The first record of a natural hybrid of the roach Rutilus rutilus and nase Chondrostoma nasus in the Danube River Basin, Czech Republic: morphological, karyological and molecular characteristics - Vetesník, L; Halacka, K; Papousek, I; Mendel, J; Simková, A (Journal of fish biology, 2009)
Morphological (meristic and morphometric traits), karyological and molecular (microsatellites, cytochrome b) analyses were performed to characterize a hybrid of the roach Rutilus rutilus and nase Chondrostoma nasus. Meristic and morphometric traits were different between hybrid and both parental species. The number of chromosomes found in hybrid specimen indicated that this individual represents the post-F(1) generation of hybrids and the microsatellite analysis of the hybrid showed the presence of variants typical for R. rutilus and C. nasus.
Keywords: Animals; Karyotyping; Česká republika; chiméra; Cyprinidae; zvířata; cytochromy b; Chimera; Cytochromes b; Rivers; mikrosatelitní repetice; karyotypizace; Czech Republic; DNA, Mitochondrial; řeky; mitochondriální DNA; Microsatellite Repeats